Fiber Quality Improvement in Upland Cotton (Gossypium hirsutum L.): Quantitative Trait Loci Mapping and Marker Assisted Selection Application - Ijaz, Babar; Zhao, Nan; Kong, Jie; Hua, Jinping (Frontiers in Plant Science, 2019)
Genetic improvement in fiber quality is one of the main challenges for cotton breeders. Fiber quality traits are controlled by multiple genes and are classified as complex quantitative traits, and existed negative relationship with yield potential, so the genetic gain is low in traditional genetic improvement for phenotypic selection. The availability of Gossypium genomic sequences facilitates the development of high-throughput molecular makers, QTL (quantitative trait loci) fine mapping and gene identification, which helps us to validate the candidate genes and to use marker assisted selection (MAS) on fiber quality in breeding program. Based on the developments of high density linkage map construction and QTL fine mapping, MAS for genomic selection have been performed for fiber quality traits in diverse populations of Upland cotton. QTL mapping combined with multi-omics approaches such as, RNA sequencing datasets to identify the differentially expressed genes have benefited the improvement of fiber quality. In this review, we discuss the application of molecular markers, QTL mapping and MAS for fiber quality improvement in Upland cotton.